The haunting of Hill House - Jackson, Shirley (New York Penguin Books, 2019)
This is the story of four seekers who arrive at a notoriously unfriendly pile called Hill House: Dr. Montague, an occult scholar looking for solid evidence of a "haunting"; Theodora, his lighthearted assistant; Eleanor, a friendless, fragile young woman well acquainted with poltergeists; and Luke, the future heir of Hill House. At first, their stay seems destined to be merely a spooky encounter with inexplicable phenomena. But Hill House is gathering its powers--and soon it will choose one of them to make its own
netflix inspiration for the netflix series
Keywords: Ghost stories; Horror fiction; ghost stories